A Normative Process Model for ICT Business Continuity Plan for Disaster Event in Small, Medium and Large Enterprises - Fadeel Sambo; Felix Olu Bankole (Institute of Advanced Engineering and Science, 2016)
Small, Medium and Large Enterprises (SMLs) are exposed to the risks of business interruption as they expand and become more dependent on Information Communication Technology (ICT) infrastructure. The current study seeks to determine why organization that have Business Continuity Plan (BCP) in place and implement regular testing of their plan still experience prolong downtime during a disaster event resulting in Service Level Agreement (SLA) not being met or major financial loss. By employing a descriptive analytics approach through a qualitative case study, the research propose a normative process model for comprehensive procedures of BCP for business leaders, ICT service managers, IS executives, data science researchers, risk managers, entrepreneur and policy makers on how to adopt strategies on effective disaster risk reduction and management in organizations. The current study offer both theoretical and practical implications for BCP in small, medium and large enterprises.